Integrating Green Economy and Islamic Finance in The Development of Halal Tourism in Lombok - Abdul Muttalib; Sebastiana Viphindrartin (Journal of Economics and Management, 2025)
The purpose of this research is to formulate an integrative framework that connects Islamic financial instruments with green economy strategies to strengthen the sustainability and inclusiveness of halal tourism development. The study employs a qualitative-descriptive approach through literature review, field observation, and semi-structured interviews with key stakeholders, including local government authorities, Islamic financial institutions, and community leaders in Lombok’s tourism sector. Data were analyzed using thematic analysis to identify patterns of synergy between green economy initiatives and Islamic finance mechanisms such as green sukuk, productive waqf, and environmental-based zakat. The findings indicate that Islamic financial instruments hold significant potential for financing sustainable tourism projects, particularly in environmental conservation, waste management, and community-based ecotourism development. The integration of green financing principles and Islamic ethical values has proven effective in enhancing environmental awareness while simultaneously strengthening the socio-economic empowerment of local communities. This study recommends the adoption of an Islamic Green Financing Model as a strategic policy framework to foster sustainable, inclusive, and resilient halal tourism. The proposed model can serve as a practical guide for policymakers, Islamic banks, and tourism stakeholders in aligning financial practices with the Maqasid al-Shariah and the Sustainable Development Goals (SDGs). Moreover, this research contributes a novel conceptual model that bridges Islamic finance and green economy perspectives within the context of halal tourism an area that remains underexplored in the existing literature. The model represents an initial contribution toward integrating Shariah-based financing with environmental and social sustainability in Muslim-majority tourism regions.